Linking urban rhythms to emotions: the inevitable emergence of emotions in the covid-19 daily life’s arrhythmia - Tzatzadaki, Olga (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2021)
The paper aims in highlighting that situations of pandemics and social disasters, such as the recent Covid-19 emergency, have an impact on daily urban rhythms and spatial practices and, as a result, a series of emotions emerge which, in the future, we will have to take seriously in consideration when creating urban policies. Henri Lefebvre, with his book Rhythmanalysis, studied the link between rhythms (cyclical & linear) and cities, in which he also described how the frequency of rhythms in spaces could manifest signs of health or illness (Arrhythmia, Polyrhythmia, Eurhythmia and Isorhythmia). Arrhythmia (otherwise indicated as non-rhythm in greek language), characterized by an unstable frequency and a lack of repetition, is a condition manifesting signs of illness, biologically, but also, according to Lefebvre’s theory, in an individual’s daily life pattern and more generally in urban rhythms. Sudden events, in the micro or macro life, could interfere with frequency and interrupt rhythm. As a result to a sudden interference of rhythm in various scales of our daily lives (economical, social, cultural, etc.), the paper proposes that, a series of negative emotions emerge on the “surface”. Undoubtedly, the emotion-protagonist in a situation of arrhythmia (biological or urban, in our case) is fear, with which individuals but also larger scale systems (cities, activities, institutions, governments, communities, etc.) have to deal with. In the Covid-19 and quarantine situation, the individual had to adapt him/herself to a new daily pattern of life and to change profoundly him/herself routine. Apparently, individuals who managed to maintain a constant daily rhythm, although in quarantine situation (in other words, being eurhythmic inside the Covid-19 arrhythmic situation), seem to be those who managed better their emotional condition. We cannot but ask ourselves, if emotions are also responsible for an individual’s and an entire community’s resilience and quality of life, why they are missing from urban policies and the urban planning agenda. Western culture was founded on the perception of “reason”, which was immediately separated from the “emotion”. In general, the role of emotion in social life and in action, has been denied, or even when it has been taken into consideration, has been negatively addressed. During the development of the western world, analysts were taught to separate cognitive and emotional qualities of judgment and tended to study cognitive rather than emotional relationships. As a result, architecture and planning, our urban space in general, followed specific functions related to our biological rhythms only. We never really understood that emotions can condition the quality of life of the individual in a high level and never tried to incorporate emotional cognition in urban planning policies. We believe more that ever that in the future and as the Covid-19 emergency showed us, we will have to deal with the consequences of negative emotions in our daily lives. Fear, anxiety and depression, all emotions caused from arrhythmic conditions in a micro (individual) or macro (entire communities) level, will eventually have to be incorporated in our future urban policies. Studying urban rhythms and their frequency, could alarm us for eventual malfunctions (micro or macro) and prepare us for their correspondent emotions. Bridging emotions to urban policies seems rather inevitable today. In particular, tackling fear through place-specific public policies seems crucial for providing a quality of life to a community, not only in biological but also in emotional terms.